2017
DOI: 10.1016/j.jpeds.2016.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain and Height Growth during Infancy, Childhood, and Adolescence as Predictors of Adult Cardiovascular Risk

Abstract: ObjectivesTo investigate independent relationships of childhood linear growth (height gain) and relative weight gain to adult cardiovascular disease (CVD) risk traits in Asian Indians.Study designData from 2218 adults from the Vellore Birth Cohort were examined for associations of cross-sectional height and body mass index (BMI) and longitudinal growth (independent conditional measures of height and weight gain) in infancy, childhood, adolescence, and adulthood with adult waist circumference (WC), blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 36 publications
2
50
1
Order By: Relevance
“…The conditional height, adjusted for previous weight in the COHORTS is also similar to the growth in LAZ adjusted for growth in WAZ in the present study. In contrast, our study is not completely consistent with a previous study, which did not formally test for differences by sex but reported greater length/height gains from 3 months to 6.5 years and 6.5 to 15 years positively associated with HOMA‐IR at 28 years in men and women, respectively . Unlike the present study, some studies found associations of growth in the first year with later insulin resistance but did not consider growth at later phases in the analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The conditional height, adjusted for previous weight in the COHORTS is also similar to the growth in LAZ adjusted for growth in WAZ in the present study. In contrast, our study is not completely consistent with a previous study, which did not formally test for differences by sex but reported greater length/height gains from 3 months to 6.5 years and 6.5 to 15 years positively associated with HOMA‐IR at 28 years in men and women, respectively . Unlike the present study, some studies found associations of growth in the first year with later insulin resistance but did not consider growth at later phases in the analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Two previous studies considered childhood or adolescent growth, and found greater BMI gains from birth to childhood and adulthood associated with higher risk of impaired glucose tolerance or diabetes in adulthood, but did not clearly distinguish the role of growth at different phases, even though the drivers and consequences of growth may vary by growth phase. One small prospective study with low follow‐up found greater length/height gains from infancy to adolescence, but not weight gain at any period, associated with higher insulin resistance based on homeostatic model assessment (HOMA‐IR) in adult men and women . Other studies have found longer leg length relative to height or attained leg length, a proxy of childhood linear growth, associated with lower risk of diabetes and longer attained trunk length, a proxy of pubertal linear growth, associated with higher risk of diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, recent data from the Vellore cohort in India showed that greater height and weight gain relative to height were associated with increased risk of a poor cardiovascular disease profile in adulthood. 31 One surprising finding was the impact of village of residence within this rural community on both BAZ and FAZ, with higher values observed in residents of the three core villages. This finding probably reflects a combination of the closer proximity to the MRC Keneba clinic and the impact of the MRC on the economy in this area (through direct employment and also indirectly).…”
Section: Discussionmentioning
confidence: 89%
“…In the COHORTS collaboration, a greater BMI gain during childhood and adolescence was associated with poorer markers of cardiometabolic health. Similarly, recent data from the Vellore cohort in India showed that greater height and weight gain relative to height were associated with increased risk of a poor cardiovascular disease profile in adulthood …”
Section: Discussionmentioning
confidence: 89%